2018
DOI: 10.1002/asia.201800645
|View full text |Cite
|
Sign up to set email alerts
|

Silica Gel as a Promoter of Sequential Aza‐Michael/Michael Reactions of Amines and Propiolic Esters: Solvent‐ and Metal‐Free Synthesis of Polyfunctionalized Conjugated Dienes

Abstract: We present an efficient, simple, metal- and solvent-free silica-gel-promoted synthesis of functionalized conjugated dienes by sequential aza-Michael/Michael reactions by starting from commercially available primary amines and propiolic esters. The scope and usefulness of the method is demonstrated for 31 examples, including a range of propiolic esters, aliphatic amines, and differently substituted aromatic amines. For aliphatic amines, the products were obtained within 0.5 to 4 h in 52 to 85 % yield, compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 91 publications
(73 reference statements)
0
6
0
Order By: Relevance
“…While intermediates 5 are easily obtainable from aliphatic amines, this is not the case with aromatic amines, which is due to their inherent weak nucleophilicity, making them as poor Michael donors . Even though the addition of an aromatic amine onto an activated alkyne is made possible under solvent-free conditions in a planetary ball mill, with ZrO 2 milling balls and SiO 2 added, our experiments showed that the solvent-free, silica gel-mediated reaction is accompanied by the formation of diene 4 (Table ), which can become the ultimate product with both aliphatic and aromatic amines . Furthermore, since the nucleophilicity of the nitrogen atom decreases further in enaminones due to the extended electron delocalization involving the aromatic ring and the double bond, we did not expect that 5 would show any tendency to react with ethyl acrylate even under basic conditions.…”
Section: Resultsmentioning
confidence: 84%
See 4 more Smart Citations
“…While intermediates 5 are easily obtainable from aliphatic amines, this is not the case with aromatic amines, which is due to their inherent weak nucleophilicity, making them as poor Michael donors . Even though the addition of an aromatic amine onto an activated alkyne is made possible under solvent-free conditions in a planetary ball mill, with ZrO 2 milling balls and SiO 2 added, our experiments showed that the solvent-free, silica gel-mediated reaction is accompanied by the formation of diene 4 (Table ), which can become the ultimate product with both aliphatic and aromatic amines . Furthermore, since the nucleophilicity of the nitrogen atom decreases further in enaminones due to the extended electron delocalization involving the aromatic ring and the double bond, we did not expect that 5 would show any tendency to react with ethyl acrylate even under basic conditions.…”
Section: Resultsmentioning
confidence: 84%
“…30 Even though the addition of an aromatic amine onto an activated alkyne is made possible under solventfree conditions in a planetary ball mill, with ZrO 2 milling balls and SiO 2 added, 31 our experiments showed that the solventfree, silica gel-mediated reaction is accompanied by the formation of diene 4 (Table 1), which can become the ultimate product with both aliphatic and aromatic amines. 22 Furthermore, since the nucleophilicity of the nitrogen atom decreases further in enaminones due to the extended electron delocalization involving the aromatic ring and the double bond, we did not expect that 5 would show any tendency to react with ethyl acrylate even under basic conditions. Therefore, we envisioned another strategy to obtain precursor 2 from aromatic amines to reverse the abovedescribed reaction sequence.…”
Section: ■ Results and Discussionmentioning
confidence: 94%
See 3 more Smart Citations